Spatial distribution and determinants of children ever born among reproductive age women in Ethiopia: spatial and multilevel analysis of 2019 mini Ethiopian demographic health survey - Ahmed, Ahmed Fentaw; Adane, Bezawit; Tsega, Tilahun Degu; Nigusu, Mekides; Sharew, Kalaab Esubalew; Molla, Abebaw; Tesfa, Mulugeta (Frontiers in Reproductive Health, 2025)
BackgroundUnderstanding population dynamics is essential since the number of children ever born (CEB) affects the growth, composition, and structure of a nation's population. The number of CEB has increased significantly, contributing to the world's rapid population growth. The spatial distribution of CEB in Ethiopia lacks recent information. Therefore, this study aimed to assess spatial distribution, and associated factors of CEB among reproductive age women in Ethiopia.MethodMini Ethiopian Demographic and Health Survey (MEDHS) 2019 data were used in this study. The study comprised 5527 (weighted) women's between the ages of 15 and 49. STATA and Aeronautical Reconnaissance Coverage Geographic Information System (ArcGIS) 10.8 software was used. The primary outcome, CEB, was categorized as “low” if fewer than five children were born and “high” if five or more children were born. Global and local Moran's Index methods were used to assess the extent of clustering. Multi-level (two-level) logistic regression analysis was used and variables with a P value less than 0.05 were considered statistical significance. Adjusted odds ratio AOR) with a 95% confidence interval (CI) was used to show the strength and direction of the association respectively.ResultsHigh number of CEB in Ethiopia was 37.46%, 95% CI (0.39–0.56) and it was spatially clustered (Moran's index = 0.59 P value <0.0001). Significant hotspots of high CEB were found in the Eastern Somali, Hadiya, Sidama, and Welayta zones. From individual-Level variables: women who were married [AOR = 3.23, 95% CI (1.48, 6.62)] were positively associated with high number of CEB. Whereas, women who were primary educated [AOR = 0.18, 95% CI (0.12, 0.27)], women who were secondary educated [AOR = 0.0.05, 95% CI (0.02, 0.13)], women's whose age at first birth after 20 year [AOR = 0.38, 95% CI (0.27, 0.51)] and women's who were using contraceptive [AOR = 0.59, 95% CI (0.44–0.78) were negatively associated with high number of CEB. From community level variables: a community with high proportion of contraceptive non user [AOR = 1.38, 95% CI (1.94–2.04)] were positively associated with high number of CEB.ConclusionBoth individual and community-level factors were significantly linked to a high number of children born. The government is advised to prioritize interventions that promote women's education, delay first births, and provide access to a range of contraceptive options, ensuring informed, voluntary choices. Empowering women to exercise reproductive autonomy, free from coercion, is key to influencing fertility outcomes effectively.